Kilka uwag o problematyce kryminalizacji nadużycia zaufania w świetle współczesnej nauki zarządzania - Solecki, Sebastian (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Trust is the determinant of the present, it becomes the dominant component of many management concepts. It is hard to imagine the current economic realities without individuals tendency to trust the entities dealing with their financial affairs. Is associated with a particular propensity to take risks; risk, which is justified by the desire for economic purposes. Abuse by a manager of the authority conferred on him or negligence has implications in the sphere of a trustee and is undoubtedly a pathological phenomenon that requires legal intervention. Criminal Law intervention characterized by ultima ratio is undoubtedly the most effective way to fight pathologies that affect negatively the economic trade. The main objective of economic criminal law should be the elimination of pathological behavior, and not development of reality or economic relations. Adjusting Art. 296 K.K. is part of the fight against a major threat, which is a breach of trust in the management relationship. This provision raises many questions, among which the basic is the question of defining the subject of the protection of Art. 296 K.K. In order to solve this problem, one must ask what the primary objective and ratio legis of discussed regulations is. We can see on the basis of the analysis that errors in this area can cause the state of things in which Art. 296 K.K. instead of providing protection affects economic trade or even inhibits it.
Keywords: zarządzanie; zaufanie; prawo karne; prawo karne gospodarcze; obrót gospodarczy